A Simple Power Management Scheme with Enhanced Stability for a Solar PV/Wind/Fuel Cell/Grid Fed Hybrid Power Supply Designed for Industrial Loads. (16th March 2014) - Saravanan, S.; Thangavel, S.
Abstract : This paper proposes a new power conditioner topology with an intelligent power management controller that integrates multiple renewable energy sources such as solar energy, wind energy, and fuel cell energy with battery and AC grid supply as backup to make the best use of their operating characteristics with better reliability than that could be obtained by single renewable energy source based power supply. The proposed embedded controller is programmed to perform MPPT for solar PV panel and WTG, SOC estimation and battery, maintaining a constant voltage at PCC and power flow control by regulating the reference currents of the controller in an instantaneous basis. The instantaneous variation in reference currents of the controller enhances the controller response as it accommodates the effect of continuously varying solar insolation and wind speed in the power management. It also prioritizes the sources for consumption to achieve maximum usage of green energy than grid energy. The simulation results of the proposed power management system with real-time solar radiation and wind velocity data collected from solar centre, KEC, and experimental results for a sporadically varying load demand are presented in this paper and the results are encouraging from reliability and stability perspectives.